Fast Timing Techniques in FLIM Applications - Hirvonen, Liisa M.; Suhling, Klaus (Frontiers in Physics, 2020)
Fluorescence lifetime imaging (FLIM) is increasingly used in many scientific disciplines, including biological and medical research, materials science and chemistry. The fluorescence label is not only used to indicate its location, but also to probe its immediate environment, via its fluorescence lifetime. This allows FLIM to monitor and image the cellular microenvironment including the interaction between proteins in their natural environment. It does so with high specificity and sensitivity in a nondestructive and minimally invasive manner, providing both structural and functional information. Time-Correlated Single Photon Counting (TCSPC) is a popular, widely used, robust and mature method to perform FLIM measurements. It is a sensitive, accurate and precise method of measuring photon arrival times after an excitation pulse, with the arrival times not affected by photobleaching or excitation or fluorescence intensity fluctuations. It has a very large dynamic range, and only needs a low illumination intensity. Different methods have been developed to advance fast and accurate timing of photon arrival. In this review a brief history of the development of these methods is given, and their merits are discussed in the context of their applications in FLIM.